DOP40 Corticosteroid discontinuation and clinical outcomes in patients with moderately to severely active Crohn's disease treated with upadacitinib. (30th January 2023) - Dubinsky, M C; D'Haens, G; Dewit, O; Juillerat, P; Panaccione, R; Fujii, T; Lacerda, A P; Dubcenco, E; Anyanwu, S; Doshi, C; Mallick, M; Garrison, A; et al.
Abstract: Background: Corticosteroids (CS) may be used for induction of remission in Crohn's disease (CD); however, side effects, toxicities, and low rates of mucosal healing may limit their long-term use. Safety and efficacy of upadacitinib (UPA), an oral selective Janus kinase inhibitor, were evaluated among patients with CD receiving UPA with CS at baseline in phase 3 clinical trials. Methods: In 2 phase 3 studies (U-EXCEL, NCT03345849; U-EXCEED, NCT03345836), patients with moderate-to-severe CD were randomized to 12-week induction with UPA 45 mg once daily (QD) or placebo (PBO). Patients who achieved clinical response to UPA 45 mg were rerandomized in U-ENDURE (NCT03345823) to UPA 30 mg QD, UPA 15 mg QD, or PBO for a 52-week maintenance period. Patients taking CS at baseline or week 0 of maintenance (end of induction) were included. A CS taper began at induction week 4 and continued during maintenance. Endpoints included the proportion of patients who discontinued CS use (CS-free) at week 12 or for ≥ 90 days prior to week 52, and achieved clinical remission by stool frequency/abdominal pain score or by Crohn's Disease Activity Index (CDAI), enhanced clinical response, decrease of at least 100 points in CDAI from baseline, endoscopic remission, and endoscopic response at week 12 and week 52. CS daily dose (in prednisone equivalent doses) was recorded. Safety was assessed through induction and maintenance. Results: Of 1021 patients evaluated, 358 (35.1%) were taking CS at baseline (mean daily prednisone equivalent dose, 23.0 mg). Greater changes from baseline in mean CS daily dose were observed with UPA vs PBO at induction week 12 (−17.3 mg vs −10.7 mg); these changes were sustained at maintenance week 52 (UPA 30 mg, −16.4 mg; UPA 15 mg, −17.4 mg; PBO, −14.7 mg). The proportion of patients who achieved a ≥ 50% reduction in CS daily dose was higher with UPA vs PBO at induction week 12 among patients taking CS at baseline (72.6% vs 48.4%) and at week 52 among patients taking CS at baseline or week 0 of maintenance (UPA 30 mg, 49.2%; UPA 15 mg, 44.4%; PBO, 11.1%). A significantly higher proportion of patients taking UPA vs PBO were CS-free and achieved clinical remission, clinical response, endoscopic response, and endoscopic remission at week 12 (Fig 1A) and week 52 (Fig 1B). Rates of adverse events (AEs), serious AEs, and discontinuation were comparable between groups (Table 1). Serious infections, opportunistic infections, and herpes zoster events were numerically higher with UPA vs PBO (Table 1). Conclusion: Patients with CD taking CS were able to taper and discontinue their CS regimen and experience clinical and endoscopic improvements with UPA treatment during the induction and maintenance periods.